The effect of stress inoculation on decrease of PTSD symptoms in veterans - E. Ahmadzadeh Aghdam; Kh. Ahmadi; R. Nooranipoor; Z. Akhavi (Afarand Scholarly Publishing Institute, 2013)
Purpose: The aim of this study was to know the effectiveness of stress inoculation on decrease of post traumatic stress disorder in Iran- Iraq (Persian Gulf) war. Method: the research theory was part-experience, for this sake 30 veterans stricken to war related PTSD veterans in mahabad randomly chosen and situated in two experiment group(15 person) and control group(15 person).data collecting was done by PCL questionnaire, which is done before and after the exam. after the pre-exam, the experiment group received 8 stress inoculation training session. data collecting analyzed by analysis of covariance. Results: the research consequences revealed that interfering with stress inoculation training in compare with control group cause decreasing of PTSD general signs and decreasing of avoidance and arousal signs. But this theory did not take effect re-experiencing signs after the interfere in veterans. Conclusion: therefore with respect to the effect of stress inoculation training on decreasing the PTSD signs, suggested that for decreasing the post traumatic stress in veterans use the upon theory at medical centers.